Health-related quality of life in localized renal masses: A matter of sparing nephrons or minimizing the incision? - Sandbergen, Laura; Spriensma, Alette Sigrid; de la Rosette, Jean J. M. C. H.; Laguna, María Pilar (Elsevier Science Inc, 2020)
Purpose: Longitudinal assessment of health-related quality of life (HRQoL) differences in patients with localized renal masses according to treatment strategy. Methods: Consecutive patients >= 18 years with localized renal masses treated with different approaches (open [O], laparoscopic [L], and percutaneous [P]) and modalities (radical nephrectomy [RN], nephron sparing surgery [NSS] and cryoablation [CA]). The SF-36, Functional Assessment of Cancer Therapy-Kidney Symptom Index-15 questionnaires and pain visual analog scale were completed pretreatment and at 1, 3, and 12 months posttreatment. Questionnaire results were stratified according to approach and treatment modality using a longitudinal multilevel linear regression model. Clinical patient and tumor characteristics, complications, and histopathology results were tested as confounders. Results: Ninety eight patients completed baseline and at least one follow-up questionnaires; 27.5%, 16.3%, 22.5%, 9.2%, 13.3%, and 11.2% patients received LNSS, ONSS, LRN, ORN, LCA, and PCA, respectively. Higher baseline SF-36 (3 domains) and Functional Assessment of Cancer Therapy-Kidney Symptom Index-15 scores were reported in L group compared with the O approach. Overall, HRQoL decreased at 1 month and gradually normalized to baseline level or higher at 1 year. For treatment modality at baseline, higher mean visual analog scale was observed in CA than RN group. A trend to decreased HRQoL was observed at 1 month for RN and NSS; thereafter, scores normalized to baseline levels or higher. Approach or treatment modality HRQoL did not change substantially when corrected for confounders. Conclusion: At short-term, HRQoL outcome favored minimally invasive treatment of RCC; at mid-term, these advantages were no longer apparent. This suggest that in selecting the best surgical treatment for the patient, oncological outcome should be the primary consideration as both approach and treatment modality result in similar HRQoL outcomes. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Health-Related Quality of Life; Localized Renal Mass; Intervention; Quality of Life Questionnaire